Physicochemical parameters and protein content in the mucus of Helix aspersa - Khrokalo, L.A.; Salitra, N.V.; Ryzhenko, N.S. (Problems of Environmental Biotechnology, 2021)
Since 2015 snail culture of species Helix aspersa Müller have been successfully introduced into Ukrainian farming. Snail mucus contains biologically active components that determine its widespread using in pharmaceutical and cosmetic products. In this work, the moisture content (98,43±0,2%) and pH = 8.2±0,1 in the snail mucus obtained from a farm company, were determined. The water-soluble fraction presence of complex proteins was determined by the biuret test, the obtained index was found to be 23.2 g/L. Experiment results are important for improving the lyophilic drying technology of mucus and further targeted applying of product.